The challenges of Georgia’s economic policy in achieving sustainable development goal 9 in the COVID-19 pandemic period - Lekashvili (ლეკაშვილი), Eka (ეკა) (University of Maribor University Press, 2022)
The increased number of financial crises and ecological catastrophes, as well as expanding inequality in the context of globalisation, have raised questions on the assumptions of mainstream economic theory and its fairness. In the context of the COVID-19 pandemic, national economies have had to face up to the new reality, which has placed great importance on the context of economic stability, security and sustainable development policies. This paper analyses the issues that need to be considered by national economic bodies in the process of achieving Sustainable Development Goal 9 (SDG 9) and transforming the economy. These issues are based on the experience gained during the COVID-19 pandemic. It is advisable to transform the economy in a way that focuses on the development of the manufacturing industry, including high-tech industries. However, these sectors should be mainly exportoriented. The development of export production should not only be based on the natural comparative advantage, but also, for the sake of expediency, on the acquired comparative advantage.
Competing in the Next Economy. A New Innovation Age Calls for a New Innovation Game (2021). USA. Council of Competitiveness. 114 pages. General Principles of EU Industrial Policy. Article 173 of the Treaty on the Functioning of the European Union. Fact Sheets in the European Union – 2021. www.europarl.europa.eu/factsheets/en . Gvelesiani, R.(2015). "Intrinsic Contradictions of Entrepreneurship Development and Selfdevelopment." International Journal of Economics and Management Engineering, Vol:9, No:3 1007- 1010. Jose M. Salazar – Xiriachs, Irmgard Nubler, Richard Kozul – Wright. (2014). Transforming Economies. Making industrial policy work for growth, jobs and development. International Labour Office. Geneva. Sobolieva, T. & Lazarenko, Y. Intellectual Property Management in the Shift Towards Open Innovation. Int. J. Economics and Business, Vol. XI, No. 2, (2019), pp.185- 195. https://dspace.tsu.ge/handle/123456789/358 Lekashvili, E. Shifted Challenges in terms of Digital Economy. Management: strategic imperatives and trends of transformations: monograph / [Sahaidak M., Sobolieva T. and all] / Edited by Mykhailo Sahaidak and Tetiana Sobolieva: Kyiv National Economic University named after Vadym Hetman, 2020. — 230, [2] p. ISBN 978–966–926–342–1; pp.8-22 (This monograph was prepared within the project of Management Department, KNEU “Transformation of business organization management” (№ 011СU001664)). Lekashvili, E., & Bitsadze, M.(2021). Chapter 4. The Role of University Spin-Offs in the Success of Research Programs. Series: Progress in Education. Volume 68. Roberta V. Nata (editor). Novapublishers. BISAC: EDU037000. DOI: https://doi.org/10.52305/WPPN2619. ISBN: 978-1-68507-230-8. ISSN:1535-4806. Lukas, S., & Kyunghoon K.(2021) After authoritarian technocracy: the space for industrial policymaking in democratic developing countries, Third World Quarterly, DOI: 10.1080/01436597.2021.1984876nt? How should industrial policies be monitored and evaluated? Taxonomy of Industrial Policy. Inclusive and Sustainable Industrial Development Working aper Series WP 08/2015. Research, Statistics and Industrial Policy Branch. 46 pages. Vesperi, W. and Gagnidze, I. (2019) Rethinking the university system: Toward the entrepreneurial university (The case of Italy), Kybernetes. Vol. 50 No. 7, pp. 2021-2041. https://doi.org/10.1108/K-12-2018-0662 Voluntary National Review Georgia 2020. Report on Implementation of the 2030 Agenda on Sustainable Development. Secretariat of the SDGs Interagency Council of Georgia. Administration of the Government of Georgia. William F. M., & Gaurav N. Industrial Policy, Information and Government Capacity. World Bank Group. Equitable Growth, Finance and Institutions Global Practice Group. May 2017. Policy Research Working Paper 8056. Transform. 2020. Resilience in the Age of COVID – 19 – an Update to the 2007 Report (2020). Council of Competitiveness. Sjoholm, F. Industrial Policy and Foreign Direct Investment. Research Institute of Industrial Economics. IFN Working Paper No.1400.2021. Social-Economic Strategy of Georgia 2020. http://www.economy.ge/uploads/ecopolitic/2020/saqartvelo_2020.pdf (Accessed 11.02.2021); Putting the EU Industrial Strategy into action. KPIs for tracking progress and benchmarking competitiveness. European Round Table for Industry. 2020. 52 pages. General principles of EU industrial Policy. Fact Sheets on the European Union – 2021. http://www.europarl.europa.eu/factsheets/en (Accessed 1.02.2021).
Keywords: economic policy, Georgia, SDG 9, COVID-19, development